Legal Analysis of the Death Penalty in Drug Crimes Case Study: (Supreme Court Decision Number 145 Pk/Pid.Sus/2016) - Hulopi, Nederlan; Suwondo, Denny (Jurnal Hukum Khaira Ummah, 2025)
Drug crimes are one of the extraordinary crimes that have a wide impact on health, social, and national security aspects. The Indonesian government has imposed strict criminal sanctions, including the death penalty, as an effort to create a deterrent effect on the perpetrators. The Supreme Court Decision Number 145 PK/PID.SUS/2016 in the name of Fredi Budiman is one of the prominent cases that shows how the death penalty is applied in large-scale drug trafficking cases. This study was conducted to analyze the legal basis for the application of the death penalty in this case. This study uses a normative legal method with a statutory approach and case studies. Data were obtained through a literature study covering statutory regulations, legal literature, and related court decisions. The analysis was conducted qualitatively by examining the consistency of the application of the law and the legal arguments used by the Supreme Court in sentencing the defendant to death. The results of the study indicate that the application of the death penalty in the Fredi Budiman case was based on the consideration of the severity of the social impact and the very large amount of narcotics. The Supreme Court considered the defendant's position as the main actor in an international narcotics syndicate and his active role in controlling drug trafficking in Indonesia. The application of the death penalty in this decision was considered to be in accordance with the provisions of applicable positive law and reflected the spirit of law enforcement against extraordinary crimes. The Supreme Court in its decision emphasized that the death penalty is still relevant to provide a deterrent effect and as an effort to protect society. However, there is debate about the effectiveness and fairness of the death penalty in the context of human rights and the possibility of improving the criminal justice system. This study recommends the importance of continuous evaluation of the application of the death penalty, especially in terms of accountability, proportionality, and guarantees of due process of law.